2022
DOI: 10.1111/jcpp.13736
|View full text |Cite
|
Sign up to set email alerts
|

Associations between emotion recognition and autistic and callous‐unemotional traits: differential effects of cueing to the eyes

Abstract: Associations between emotion recognition and autistic and callousunemotional traits: differential effects of cueing to the eyes. Journal of Child Psychology and Psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…In emotion recognition tasks, participants typically spend more time looking at eyes than any other region of the face (Scheller et al, 2012). However, studies have found that children and adolescents with high CU behaviors look less at the eye region of fearful faces, and that this reduced looking contributes to poor fear recognition in these children (Dadds et al, 2006(Dadds et al, , 2008Leno et al, 2022). Prior work has also shown that children with high CU behaviors make less eye contact with their parents in naturalistic child-parent dyadic interactions (Dadds et al, 2011), supporting a working hypothesis that CU traits may arise from a failure to attend to caregivers' eyes in early life (Dadds et al, 2008), a behavioral pattern that may then generalize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In emotion recognition tasks, participants typically spend more time looking at eyes than any other region of the face (Scheller et al, 2012). However, studies have found that children and adolescents with high CU behaviors look less at the eye region of fearful faces, and that this reduced looking contributes to poor fear recognition in these children (Dadds et al, 2006(Dadds et al, , 2008Leno et al, 2022). Prior work has also shown that children with high CU behaviors make less eye contact with their parents in naturalistic child-parent dyadic interactions (Dadds et al, 2011), supporting a working hypothesis that CU traits may arise from a failure to attend to caregivers' eyes in early life (Dadds et al, 2008), a behavioral pattern that may then generalize.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that decreased eye looking may be related to fear recognition deficits in children with high CU behaviors. In one set of studies, experimental and real-world eye looking was positively associated with fear recognition in children with high CU behaviors (Dadds et al, 2008(Dadds et al, , 2011, and cueing children with high CU behaviors to look at eyes specifically improved their fear recognition performance (Carter Leno et al, 2022). However, not all research has found associations between high CU behaviors and reduced eye looking (e.g., Hartmann & Schwenck, 2020), suggesting a need for additional research on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…The studies included within this review were characterised by multiple difficulties with measurement, including lack of validated measures for identifying psychopathic traits within autistic individuals, highlighting this as an area requiring attention. There was a lack of intervention studies, however there was some evidence to suggest that interventions to improve eye contact may be a helpful strategy to improve emotion recognition in psychopathic individuals but may have a detrimental impact for autistic individuals ( 42 ). The impact of such interventions for individuals with both psychopathy and autism is unclear but clinicians should be aware of the different underlying mechanisms and consider this with implementation of any emotion recognition strategies used.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the role of eye gaze on emotion recognition ( 33 , 34 , 40 , 42 ). Bours et al.…”
Section: Autism and Callous And Unemotional Traits In Childrenmentioning
confidence: 99%
“…While some impairment in recognition is often found in research as being related to CU traits, the extent of the impairments is unclear. For instance, while some studies found that impairment was evident to some extent across many different emotions [5,14,22,[26][27][28], other studies mainly focused on deficits in the processing of negative emotional stimuli [19], and, in particular, facial depictions of distress, such as sadness [23,24,29] and fear [15,21,29,30]. Moreover, not all studies have confirmed these impairments; for instance, some studies have found a positive association between CU traits and fear recognition [24,[31][32][33].…”
Section: Emotion Recognition and Cu Traitsmentioning
confidence: 99%